2012
DOI: 10.7897/2277-4343.03523
|View full text |Cite
|
Sign up to set email alerts
|

Folk Remedies of Medicinal Plants for Snake Bites, Scorpion Stings and Dog Bites in Eastern Ghats of Kolli Hills, Tamil Nadu, India

Abstract: Folk remedies practiced by the tribes of Kolli Hills of Eastern Ghats, Tamil Nadu, India were documented. Around 30 folk remedies for snake bite, 18 for scorpion sting and 4 for dog bite were reported in this study. Details of the plants used for snake bite, scorpion sting and dog bite with local name, parts used and methods of preparation, dosage and the mode of administration were discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Ailanthus excels stem bark extract is given by Bhil Tribes of Bibdod Madhya Pradesh, India 13 . Aloe vera whole plant is used in Eastern Ghat of Koli Hill Tamil Nadu, India for the treatment of Typhoid 14 . The study revitalizes the traditional system of medicine in order to achieve selfreliance in health care and health for all by analysing the antimicrobial property of aqueous extracts of Aloe vera and to assess the reason for inhibition of growth of pathogenic organisms by DNA and protein analysis.…”
Section: Folk Medicinementioning
confidence: 99%
See 1 more Smart Citation
“…Ailanthus excels stem bark extract is given by Bhil Tribes of Bibdod Madhya Pradesh, India 13 . Aloe vera whole plant is used in Eastern Ghat of Koli Hill Tamil Nadu, India for the treatment of Typhoid 14 . The study revitalizes the traditional system of medicine in order to achieve selfreliance in health care and health for all by analysing the antimicrobial property of aqueous extracts of Aloe vera and to assess the reason for inhibition of growth of pathogenic organisms by DNA and protein analysis.…”
Section: Folk Medicinementioning
confidence: 99%
“…The ethanolic extract showed most susceptible activity against S. aureous and B. subtilis where as P. aeruginosa was the most resistant bacteria strain 70 . Ricinus communis seed is used in Eastern Ghat of Koli Hill Tamil Nadu, India 71 . Antimicrobial test with eleven bacteria demonstrated that the extracts of cell suspension culture of R. communis L. cv.…”
Section: Folk Medicinementioning
confidence: 99%
“…Haidara et al (2006) 9 has conducted pharmacological studies that prove that casticin have anti-inflammatory, antitumor, cytotoxics, antiasthmatic, analgesic, and casticin itself contained in the plant Legundi. Prabu and Kumuthakalavalli in their article mentions that vitex trifolia have medicinal use for diarrhoea, urticaria, cellulites, abscess, carbuncle, and eczema 10 . In 2013, we reported that the ethanol extract of Vitex sp.…”
Section: Introductionmentioning
confidence: 99%
“…Man has been dependent on plant based traditional medicines since time immemorial. This knowledge of using plants to obtain medicines to treat various ailments has been gradually accumulated and transmitted from generation to generation in the course of several centuries, forming the basis of various indigenous medicinal systems such as Ayurveda, Unani and Siddha 4 . During the last few decades, an increasing interest in the study of traditional uses of medicinal plants has been witnessed in different parts of the world, mainly due to high cost and other disadvantages associated with allopathic system of medicine .…”
Section: Introductionmentioning
confidence: 99%